Identifikasi Jamur Endofit Asal Tanaman Tebu (Saccharum officinarum L.) Dalam Menghambat Xanthomonas albilineans L. Penyebab Penyakit Vaskular Bakteri - Siti Hardianti Wahyuni (Universitas Teuku Umar, 2018)
Identification of endophytic fungi from sugarcane as biocontrol agents to control bacterial vascular (Xanthomonas albilineans) on sugarcane. This research aims to identification endophytic fungi to against X. albilineans on sugarcane. The research was conducted at Plant Disease Laboratory, Agroecotechnology Program Study, Faculty of Agriculture, University of Sumatera Utara, Medan from May to August 2013. The results showed all the endophytic fungi used (Penicillium sp.,Curvularia sp., Aspergillus sp., Fusarium sp., Cephalosporium sp.,) potential as biological agents to control bacterial vascular wilt on sugarcane. The domination endophytic fungi from sugarcane identificated Penicillium sp. and Aspergillus sp. Keywords: Sugarcane, Xanthomonas albilineans, endophytic fungi, identification